ผลของการเรียนรู้เชิงประสบการณ์ต่อความรู้ การคัดกรองและการให้คำแนะนำในการป้องกันโรคมะเร็งลำไส้ในอาสาสมัครสาธารณสุข ประจำหมู่บ้าน - อำพิกา คันทาใจ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Nowadays, the incidence of colorectal cancer in Thailand has been increasing. Screening and advising on the prevention of colorectal cancer are very important. Quasi–experimental research with two groups, pretest-posttest design was used in this research, which aimed to study the effects of experiential learning on knowledge, screening, and advising on colorectal cancer prevention among village health volunteers. The sample group was village health volunteers from 9 sub-districts in Ko Kha district, Lampang province. There were 40 persons in total. 20 of them were in a group with experiential learning, and the other 20 were in a controlled group receiving advice from public health officers regularly. Research tools were divided into 2 parts: 1) The experimental tools consisted of (i) an experiential learning package of knowledge, screening practice and advice regarding prevention colorectal cancer of the village health volunteers, (ii) the experiential learning tools, and (iii) a manual of knowledge, screening practice, and advice regarding prevention colorectal cancer for the village health volunteers. 2) The collecting data consisted of: demographic data, a questionnaire based on prevention of colorectal cancer, screening practice observation form, and advising practice observation form based on prevention of colorectal cancer. Descriptive statistics, McNemar test, and Fisher’s Exact test were used for data analysis. Results showed that: After attending the experiential learning, the level of knowledge, screening practice, and advising practice on the prevention of colorectal cancer among the village health volunteers was statistically significantly higher than before participation in the experiential learning (p < .001). After attending the experiential learning, the level of knowledge, screening practice and advising practice on the prevention of colorectal cancer among the village health volunteers of the experimental group was statistically significantly higher than the control group (p = .003, p < .001, p < .001) respectively. The results of this study illustrate that the experiential learning of the village health volunteers affected the sample groups’ knowledge of colorectal cancer, leading to the acquisition of more accurate skills in the screening of and advising on prevention of colorectal cancer.